Management: Meanings, Methods, and Moxie - Dubin, Robert (Academy of Management Review, 1982)
Studies of organizations and management have not produced as much solid knowledge as should have been forthcoming. This is attributed to problems with theorizing; limited focus on data sources and methods of analysis; and lack of courage to utilize imagination in scholarly work. Examples are provided to support these allegations. A generally optimistic conclusion suggests that the study of organizations is a great growth area for the investment of human intelligence.